O repertório de trombone baixo nas universidades brasileiras: uma proposta de classificação de dificuldades - Silva Junior, Milton Marciano da (2018)
The classification of repertoire by levels of difficulty, using technical and musical parameters, is a practice consolidated in several countries and serves as a tool in teaching planning. However, this practice is not widespread in Brazil. Therefore, the objective of this research is to investigate the repertoire for solos bass trombone used in undergraduate programs in Brazilian Federal universities and propose a grading system to these pieces. The system was based on previously defined parameters; we observe range, rhythm and metric, articulation, duration, tempo, and key signature to determine the classification level. The data collection was done through bibliographical and documentary studies, prioritizing works dealing with classification of repertoire, its level of difficulty and identification of specifics challenges. Inevitably, we understand that gaps and inconsistencies will remain due to the substantial number of variables.